2016
DOI: 10.1002/2015jd024343
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Black Saturday 2009 smoke plume with an interactive composition‐climate model: Sensitivity to emissions amount, timing, and injection height

Abstract: We simulated the high‐altitude smoke plume from the early February 2009 Black Saturday bushfires in southeastern Australia using the NASA Goddard Institute for Space Studies ModelE2. To the best of our knowledge, this is the first single‐plume analysis of biomass burning emissions injected directly into the upper troposphere/lower stratosphere (UTLS) using a full‐complexity composition‐climate model. We compared simulated carbon monoxide (CO) to a new Aura Tropospheric Emission Spectrometer/Microwave Limb Soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 69 publications
(213 reference statements)
1
19
0
Order By: Relevance
“…Although the focus of this study is on climatological features, rather than individual case studies of events, it is noted that the compound event days include both of the cases observed in Australia for which the pyroconvection was strong enough to inject biomass into the stratosphere; for the Canberra fires in eastern Australia during January 2003 and Black Saturday in southeastern Australia during February 2009 (Cunningham & Reeder, 2009;Dowdy et al, 2017;Field et al, 2016;Fromm et al, 2006;McRae et al, 2013;Mills & McCaw, 2010). For the Canberra and Black Saturday events, CH values are 13.5 and 13.4, respectively, and FFDI values are 56 and 136, respectively, all of which are the highest on record at each location for the study period 1979-2016 with the exception of FFDI at Canberra (which is above the 99.8th percentile for that location).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the focus of this study is on climatological features, rather than individual case studies of events, it is noted that the compound event days include both of the cases observed in Australia for which the pyroconvection was strong enough to inject biomass into the stratosphere; for the Canberra fires in eastern Australia during January 2003 and Black Saturday in southeastern Australia during February 2009 (Cunningham & Reeder, 2009;Dowdy et al, 2017;Field et al, 2016;Fromm et al, 2006;McRae et al, 2013;Mills & McCaw, 2010). For the Canberra and Black Saturday events, CH values are 13.5 and 13.4, respectively, and FFDI values are 56 and 136, respectively, all of which are the highest on record at each location for the study period 1979-2016 with the exception of FFDI at Canberra (which is above the 99.8th percentile for that location).…”
Section: Discussionmentioning
confidence: 99%
“…A number of disastrous fire events associated with pyroconvection have recently occurred in Australia (Cunningham & Reeder, 2009;Dowdy et al, 2017;Field et al, 2016;Fromm et al, 2006;McRae et al, 2013;Mills & McCaw, 2010) and other regions of the world (Fromm et al, 2010;Lang & Rutledge, 2006;Lang et al, 2014;Peterson et al, 2017;Rosenfeld et al, 2007). Extreme fire events associated with pyroconvection have only been discussed relatively recently in the literature, with available reports of PyroCbs primarily occurring in recent decades (Fromm et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To represent the vertical variation in the smoke plumes and to allow for direct stratospheric injection of pyroCb smoke emissions, we must incorporate injection heights with the pyroCb emission estimates from Peterson et al (2018). Altitude of emission injection has been shown in many previous studies to be significant in determining aerosol transport and residence time (Colarco et al, 2004;Field et al, 2016;Leung et al, 2007;Turquety et al, 2007;Val Martin et al, 2010). Similarly, modeled radiative forcings can also be sensitive to emission injection heights (Ban-Weiss et al, 2012;.…”
Section: Creation Of 3-d Pyrocb Emissionsmentioning
confidence: 99%
“…Wildfires with extreme pyroconvection have recently caused severe impacts in Australia, including the deaths of many people. Examples include the Black Saturday (February 2009) and Canberra fires (January 2003) in southern Australia which had pyroconvection strong enough to produce pyroCb that injected smoke into the stratosphere 1,6,12,13 . This volcano-like process has also been documented for extreme pyroconvection events in other regions including in North America 3,7,1416 .…”
Section: Introductionmentioning
confidence: 99%